COVID-19 in an adolescent with cerebral palsy: A case report (Research, Society and Development, 2021)
Background: Children have been impacted by COVID-19 pandemics and biological mechanisms of host response are under active investigation worldwide to develop better treatment plans. Children with cerebral palsy (CP) diagnosis are less studied, although they present increased risk for COVID-19 disease (COVID-CP). Here, we aim to report the diagnosis and treatment plan to further improve clinical protocols for COVID-CP patients. Case Presentation: This case report describes a 12-year-old male diagnosed with neuropsychomotor developmental delay, chronic non-progressive encephalopathy, spastic tetraparesis, epilepsy and recently COVID-19 disease.  SARS-CoV-2 viral detection was assayed by RT-PCR swab (nasopharynx and oropharynx) concomitantly with family members. Subject presented symptoms after 3 days of confirmed diagnostics and presented positive viral even after 2 weeks of testing, suggesting long exposure to the virus. The unique signs and symptoms led the treatment plan to focus on maintaining oxygen levels, management of severe lung phenotype, and control of increased seizures. In addition, levels of inflammatory cytokines were monitored to predict risk of cytokine storm, risk for multisystemic inflammatory syndrome (MISC), and need for continuous hospitalization. A pharmacological treatment protocol for asthma was implemented in association to vigorous monitoring by caregivers and family members. The course of the viral phase, from its onset to negativity, was longer than the average time of 14 days. Conclusion: Clinical manifestations, complementary exams and treatment are discussed to better improve protocols of COVID-CP patients.